Design of Piano -playing Robotic Hand - Lin Jen-Chang; Hsin-Cheng Li; Kuo-Cheng Huang; Shu-Wei Lin (IAES International Journal of Robotics and Automation (IJRA), 2014)
Unlike the market slowdown of industrial robots, service & entertainment robots have been highly regarded by most robotics reseach and market research agencies. In this study we developed a music playing robot (which can also work as a service robot) for public performance. The research is mainly focused on the mechanical and electrical control of piano-playing robot, the exploration of correlations among music theory, rhythm and piano keys, and eventually the research on playing skill of keyboard instrument. The piano-playing robot is capable of control linear motor, servo-motor and pneumatic devices in accordance with the notes and rhythm in order to drive the mechanical structure to proper positions for pressing the keys and generating music. The devices used for this robot are mainly crucial components produced by HIWIN Technology Corp. The design of robotic hand is based on the direction of anthropomorphic hand such that five fingers will be used for playing piano. The finger actuations include actions of finger rotation, finger pressing, and finger lifting; time required for these 3 stages must meet the requirement of rhythm. The purpose of entertainment robot can be achieved by playing electric piano with robotic hand, and we hope this research can contribute to the development of domestic entertainment music playing robots.